Mixed methods to evaluate knowledge, attitudes and practices (KAP) towards rabies in central and remote communities of Moramanga district, Madagascar. - Claire Leblanc; Daouda Kassié; Mendrika Ranaivoharimina; Elliot Fara Nandrasana Rakotomanana; Reziky Tiandraza Mangahasimbola; Anjasoa Randrianarijaona; Ravo Ramiandrasoa; Alphonse José Nely; Nivohanitra Perle Razafindraibe; Soa Fy Andriamandimby; Dany Bakoly Ranoaritiana; Virginie Rajaonarivony; et al. (Public Library of Science (PLoS), 2024)
Control of dog-mediated rabies relies on raising awareness, access to post-exposure prophylaxis (PEP) and mass dog vaccination. To assess rabies awareness in Moramanga district, Madagascar, where rabies is endemic, two complementary quantitative and qualitative approaches were carried out in 2018. In the quantitative approach, a standardized questionnaire was administered to 334 randomized participants living in 170 households located less than 5 km from the anti-rabies treatment center (ARTC) located in Moramanga city (thereafter called the central area), and in 164 households located more than 15 km away from the ARTC in two rural communes (thereafter called the remote area). Logistic regression models were fitted to identify factors influencing knowledge and practice scores. The qualitative approach consisted in semi-structured interviews conducted with 28 bite victims who had consulted the ARTC, three owners of biting dogs, three ARTC staff and two local authorities. Overall, 15.6% (52/334) of households owned at least one dog. The dog-to-human ratio was 1:17.6. The central area had a significantly higher dog bite incidence (0.53 per 100 person-years, 95% CI: 0.31-0.85) compared to the remote area (0.22 per 100 person-years, 95% CI: 0.09-0.43) (p = 0.03). The care pathway following a bite depended on wound severity, how the dog was perceived and its owner's willingness to cover costs. Rabies vaccination coverage in dogs in the remote area was extremely low (2.4%). Respondents knew that vaccination prevented animal rabies but owners considered that their own dogs were harmless and cited access and cost of vaccine as main barriers. Most respondents were not aware of the existence of the ARTC (85.3%), did not know the importance of timely access to PEP (92.2%) or that biting dogs should be isolated (89.5%) and monitored. Good knowledge scores were significantly associated with having a higher socio-economic status (OR = 2.08, CI = 1.33-3.26) and living in central area (OR = 1.91, CI = 1.22-3.00). Good practice scores were significantly associated with living in central area (OR = 4.78, CI = 2.98-7.77) and being aware of the ARTC's existence (OR = 2.29, CI = 1.14-4.80). In Madagascar, knowledge on rabies was disparate with important gaps on PEP and animal management. Awareness campaigns should inform communities (i) on the importance of seeking PEP as soon as possible after an exposure, whatever the severity of the wound and the type of biting dog who caused it, and (ii) on the existence and location of ARTCs where free-of-charge PEP is available. They should also encourage owners to isolate and monitor the health of biting dogs. Above all, awareness and dog vaccination campaigns should be designed so as to reach the more vulnerable remote rural populations as knowledge, good practices and vaccination coverage were lower in these areas. They should also target households with a lower socio-economic status. If awareness campaigns are likely to succeed in improving access to ARTCs in Madagascar, their impact on prompting dog owners to vaccinate their own dogs seems more uncertain given the financial and access barriers. Therefore, to reach the 70% dog vaccination coverage goal targeted in rabies elimination programs, awareness campaigns must be combined with free-of-charge mass dog vaccination.